A charge-coupled device photometric study of south hemispheric contact binary AE Phoenicis - He, J. J. (2009)
The complete charge-coupled device light curves in B, V, R, and I bands of the short-period binary system, AE Phe, are presented. It is found that the light curves of AE Phe belong to typical EW-type light variation. Photometric solutions were derived by using the 2003 version of the Wilson–Devinney code. It showed that AE Phe is a Wsubtype shallow-contact system (f = 14.6%(±0.5%)) with a mass ratio of q = 2.5491(±0.0092). The temperature difference between the two components is 227 K. Analysis of the O − C curve suggests that the period of AE Phe shows a long-term continuous increase at a rate of dP /dt = +6.17(±0.44) × 10−8 days year−1. The longterm period increase, the marginal-contact configuration, and the astrophysical parameters of the binary system, all suggest that it is a shallow-contact binary undergoing a thermal relaxation oscillation evolving into a detached binary.